Experimental Evidence From Active Placement Efforts Among Unemployed in Sweden. (June 2014) - Hägglund, Pathric
This article uses data from a field experiment in Sweden to analyze the effects of active placement efforts. In particular, the relative efficiency between combining job-search monitoring and job-search assistance, and monitoring alone, is analyzed. Although the impact estimates are generally imprecisely estimated, a general conclusion is that placement programs are effective policies in increasing the job exit rate for various groups of unemployed. I find that monitoring of job search is an efficient method to increase off-unemployment exit rate both alone and combined with job-search assistance services. The results, however, indicate that the combined services generate more permanent job exits.